2020
DOI: 10.1039/d0ra02687e
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and structural characterization of lithiation in spray deposited ordered mesoporous titania as an anode for Li ion batteries

Abstract: A combination of electrochemical and structural characterization techniques were used to study the lithiation in spray deposited amorphous mesoporous titania.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…The pore diameter and crystallite size of the films are listed in Table S2, Supplementary Materials . In a recent publication, where the electrochemical properties of the films prepared here were studied, it was shown that the mesoporous structures are retained after milling, mixing, and repeated electrochemical cycling [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The pore diameter and crystallite size of the films are listed in Table S2, Supplementary Materials . In a recent publication, where the electrochemical properties of the films prepared here were studied, it was shown that the mesoporous structures are retained after milling, mixing, and repeated electrochemical cycling [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ordered mesoporous titania films, deposited by spray-coating, have also been fabricated as anode materials in lithium-ion batteries 88 . The material exhibits a high capacity of 680 mA h g −1 at the first discharge, which, however, quickly decreases with the cycles to stabilize at around 170 mA h g −1 after 50 cycles.…”
Section: Negative Electrodes and Energy Storage Devices For Lithium B...mentioning
confidence: 99%
“…Besides graphene, BN 87 and W 2 S 88 nanosheets have also been successfully incorporated via one-pot self-assembly into mesoporous ordered titania films. The bidimensional materials can be easily dispersed in the precursor sol and remain homogeneously dispersed into the mesoporous films that keep the organization of the pores.…”
Section: Integrating the Flatland With Mesoporous Films Advanced Sensingmentioning
confidence: 99%